Предмет: Математика,
автор: Andrej105112
разложите на множители a^2b^2(b-a)+b^a^2(c-b)+c^2a^2(a-c) срочно!
Ответы
Автор ответа:
0
прежде всего за скобки а квадрат:
a^2*(b^3-b^2*a+b^2c-b^3+c^2a-c^3)=a^2*(-b^2a+b^2c+c^2a-c^3)=
a^2*((-a+c)*b^2+c^2a-c^3)+c^2*(a-c))=a^2*(a-c)*(c^2-b^2)=
a^2*(a-c)*(c-b)*(c+b)
Ответ: a^2*(a-c)*(c-b)*(c+b)
a^2*(b^3-b^2*a+b^2c-b^3+c^2a-c^3)=a^2*(-b^2a+b^2c+c^2a-c^3)=
a^2*((-a+c)*b^2+c^2a-c^3)+c^2*(a-c))=a^2*(a-c)*(c^2-b^2)=
a^2*(a-c)*(c-b)*(c+b)
Ответ: a^2*(a-c)*(c-b)*(c+b)
Похожие вопросы
Предмет: Русский язык,
автор: gulzirakuvvatova4
Предмет: Биология,
автор: murzabaevaluiza231
Предмет: Физика,
автор: danilkozlov96
Предмет: Физика,
автор: 14ana01
Предмет: Математика,
автор: катя1362